Full C-Band Tunable V-Cavity-Laser based TOSA and SFP Transceiver Modules - Saravanan K; V Mathivanan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
We report the latest development in tunable transmitter optical sub-assembly (TOSA) and small form-factor pluggable (SFP) transceivers based on simple and compact V-cavity laser (VCL), aiming for low-cost deployment in metro, access and data center networks. The VCL employs a half-wave coupler to achieve high side-mode suppression ratio (SMSR) and the Vernier effect to achieve a wide wavelength tuning range. Full C-band tuning from 1529.55-nm to 1566.31-nm with SMSR above 36 dB is demonstrated. Since the laser does not involve any grating or epitaxial regrowth, and has a simple tuning algorithm, it allows simpler processes for fabrication and testing as compared to other widely tunable laser structures. Compact TOSAs and SFP transceiver modules have been developed for full C-band tuning with up to 93 channels at 50 GHz spacing. Transmission experiments are carried out for direct modulation with data rates from 2.5 Gbps to 8.5 Gbps. The results of reliability tests of the modules are also presented.